Scenarios of Deoxygenation of the Eastern Tropical North Pacific During the Past Millennium as a Window Into the Future of Oxygen Minimum Zones - Choumiline, Konstantin; Pérez-Cruz, Ligia; Gray, Andrew B.; Bates, Steven M.; Lyons, Timothy W. (Frontiers in Earth Science, 2019)
Diverse studies predict global expansion of Oxygen Minimum Zones (OMZs) as a consequence of anthropogenic global warming. While the observed dissolved oxygen concentrations in many coastal regions are slowly decreasing, sediment core paleorecords often show contradictory trends. This is the case for numerous high-resolution reconstructions of oxygenation in the Eastern Tropical North Pacific (ETNP). While major shifts in redox conditions of the ETNP are dominated by glacial-interglacial cycling, important fluctuations also occur in response to minor climatic and oceanographic perturbations. It is important to understand these scenarios of past redox variation, as they are the closest analogues for near future climate and oceanographic change. We present recently collected sediment core proxy records from the Gulf of California in which we reproduce the variability of productivity and oxygenation of the ETNP OMZ during the past millennium. We emphasize paleoproductivity (Corg, Ni, Baexcess) and paleoredox indicators (Mo, V, Uauth) in sediment cores collected in Alfonso and La Paz basins and compare these OMZ records with other archives of the Eastern Pacific. Our findings indicate that the OMZ expanded in response to increased upwelling and productivity during cold intervals around 1830, 1680, and 1500 years AD (evidenced by higher P, Ni, Mo, V, and Uauth). The most hypoxic times corresponded to the beginning of the Little Ice Age (expressed in elevated Mo). Significant OMZ contractions occurred around 1300, 1650, and 1900s AD after reoxygenation events that were instigated by low productivity (lower Ni, Mo, V, and Uauth). The mechanisms that control decadal-to-centennial oxygen variability in the ETNP remain unidentified but are likely influenced by solar forcing not only driving migrations of the Intertropical Convergence Zone (ITCZ) but more importantly changes in the intensity of the Pacific Walker Circulation (PWC). During the Little Ice Age solar irradiance was at its lowest for the past millennium, which strengthened the PWC. This pattern contributed to more frequent La Niña-like conditions, which enhanced upwelling of nutrient-rich waters in the west coast of North America, driving productivity and reducing bottom oxygen levels, as seen in our ETNP records.